Systemic priming and intranasal booster with a BcfA-adjuvanted acellular pertussis vaccine generates CD4+ IL-17+ nasal tissue resident T cells and reduces B. pertussis nasal colonization - Yount, Kacy S.; Hall, Jesse M.; Caution, Kyle; Shamseldin, Mohamed M.; Guo, Myra; Marion, Keirsten; Fullen, Audra R.; Huang, Yimin; Maynard, Jennifer A.; Quataert, Sally A.; Deora, Rajendar; Dubey, Purnima (Frontiers in Immunology, 2023)
Resurgence of pertussis, caused by Bordetella pertussis, necessitates novel vaccines and vaccination strategies to combat this disease. Alum-adjuvanted acellular pertussis vaccines (aPV) delivered intramuscularly reduce bacterial numbers in the lungs of immunized animals and humans, but do not reduce nasal colonization. Thus, aPV-immunized individuals are sources of community transmission. We showed previously that modification of a commercial aPV (Boostrix) by addition of the Th1/17 polarizing adjuvant Bordetella Colonization Factor A (BcfA) attenuated Th2 responses elicited by alum and accelerated clearance of B. pertussis from mouse lungs. Here we tested whether a heterologous immunization strategy with systemic priming and mucosal booster (prime-pull) would reduce nasal colonization in mice. Here we show that prime-pull immunization with Boostrix plus BcfA (aPV/BcfA) generated IFNγ+ and IL-17+ CD4+ lung resident memory T cells (TRM), and CD4+IL-17+ TRM in the nose. In contrast, aPV alone delivered by the same route generated IL-5+ CD4+ resident memory T cells in the lungs and nose. Importantly, nasal colonization was only reduced in mice immunized with aPV/BcfA by the prime-pull regimen. These results suggest that Th17 polarized TRM generated by aPV/BcfA a may reduce nasal colonization thereby preventing pertussis transmission and subsequent resurgence.